PENGARUH DUKUNGAN SOSIAL DAN STUDENT SUBJECTIVE WELL-BEING TERHADAP SCHOOL ENGAGEMENT SANTRIWATI AISYAH ISLAMIC BOARDING SCHOOL - Sarah Labibah; Linda Mora; Haryanti Mustika (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2025)
This study aims to analyze the influence of social support and student subjective well-being on school engagement of female students at Aisyah Islamic Boarding School. In this study, the research method used is quantitative involving 90 female students as respondents. Data were collected through a scale that measures the level of school engagement, namely the school engagement scale, social support, namely the perceived social support, and student subjective well-being, namely the student subjective well-being questionnaire. The results of the study showed a significant value of the social support variable of 0.208 > 0.05, which means there is no influence of social support on school engagement of female students at Aisyah Islamic Boarding School. The significant value of student subjective well-being is 0.000 < 0.05, which means there is an influence of student subjective well-being on school engagement of female students at Aisyah Islamic Boarding School. Then simultaneously social support and student subjective well-being showed a significant value of 0.000 < 0.05, which means there is an influence of social support and student subjective well-being simultaneously on school engagement of female students at Aisyah Islamic Boarding School. The magnitude of the influence of social support and student subjective well-being on school engagement in female students at Aisyah Islamic Boarding School is 56.9%. Penelitian ini bertujuan untuk menganalisis pengaruh dukungan sosial dan student subjective well-being terhadap school engagement santriwati di Aisyah Islamic Boarding School. Dalam penelitian ini, metode penelitian yang digunakan adalah kuantitatif yang melibatkan 90 santriwati sebagai responden. Data dikumpulkan melalui skala yang mengukur tingkat school engagement yaitu school engagement scale, dukungan sosial yaitu the perceived social suport, dan student subjective well-being yaitu student subjective well-being questionnare. Hasil penelitian menunjukkan nilai signifikan dari variabel dukungan sosial sebesar 0.208 > 0.05, yang artinya tidak ada pengaruh dukungan sosial terhadap school engagement santriwati Aisyah Islamic Boarding School. Nilai signifikan dari student subjective well-being adalah sebesar 0.000 < 0.05, yang artinya ada pengaruh student subjective well-being terhadap school engagement santriwati Aisyah Islamic Boarding School. Kemudian secara simultan dukungan sosial dan student subjective well-being menunjukkan nilai signifikan sebesar 0.000 < 0.05, yang artinya ada pengaruh dukungan sosial dan student subjective well-being secara bersamaan terhadap school engagement santriwati Aisyah Islamic Boarding School. Besaran pengaruh dukungan sosial dan student subjective well-being terhadap school engagament pada santriwati Aisyah Islamic Boarding School adalah sebesar 56.9%.